Estimating the Implicit Inflation Target : An Application to U.S. Monetary Policy - Leigh, Daniel (Washington, D.C. : International Monetary Fund, 2005)
This paper proposes a new method of estimating the Taylor rule with a time-varying implicit inflation target and a time-varying natural rate of interest. The inflation target and the natural rate are modeled as random walks and are estimated using maximum likelihood and the Kalman filter. I apply this method to U.S. monetary policy over the past 25 years and find considerable time variation in the implicit target, confirming hypotheses about "opportunistic disinflation" and the recent "deflation scare.".
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet